Networks with group counterproposals - Ricardo Nieva (Fondazione Eni Enrico Mattei (FEEM), 2008)
We study two n-player sequential network formation games with externalities. Link formation is tied to simultaneous transfer selection in a Nash demand like game in each period. Players in groups can counterpropose. We give necessary and sufficient conditions for efficiency in terms of cyclical monotonicity. The n-player group version always yields efficiency.
Keywords: C71; C72; C73; C78; 330; Efficiency; Bargaining Protocol; Counterproposals; Network Formation; Transfers; Externalities; Groups; Coalitions